Characterizing Strategic Design Processes in Relation to Definitions of Strategy from Military, Business and Management Studies. (3rd July 2020) - Simeone, Luca
Abstract: This paper reviews existing characterizations of strategy from military, business and management studies and examines how these characterizations may help inform strategic design processes. The paper serves as an entry point for both design researchers and practitioners interested in understanding the rich and nuanced perspectives that such varied characterizations of strategy may provide.